Increased susceptibility to otitis media in a Splunc1-deficient mouse model - Jennifer A. Bartlett; David K. Meyerholz; Christine L. Wohlford-Lenane; Paul W. Naumann; Nita H. Salzman; Paul B. McCray (Disease Models & Mechanisms, 2015)
Otitis media (inflammation of the middle ear) is one of the most common diseases of early childhood. Susceptibility to otitis is influenced by a number of factors, including the actions of innate immune molecules secreted by the epithelia lining the nasopharynx, middle ear and Eustachian tube. The SPLUNC1 (short palate, lung, nasal epithelial clone 1) protein is a highly abundant secretory product of the mammalian nasal, oral and respiratory mucosa that is thought to play a multifunctional role in host defense. In this study we investigated Splunc1 expression in the ear of the mouse, and examined whether this protein contributes to overall host defense in the middle ear and/or Eustachian tube. We found that Splunc1 is highly expressed in both the surface epithelium and in submucosal glands in these regions in wild-type mice. In mice lacking Splunc1, we noted histologically an increased frequency of otitis media, characterized by the accumulation of leukocytes (neutrophils with scattered macrophages), proteinaceous fluid and mucus in the middle ear lumens. Furthermore, many of these mice had extensive remodeling of the middle ear wall, suggesting a chronic course of disease. From these observations, we conclude that loss of Splunc1 predisposes mice to the development of otitis media. The Splunc1−/− mouse model should help investigators to better understand both the biological role of Splunc1 as well as host defense mechanisms in the middle ear.